Classroom observation as supervisory practice in selected public secondary schools in Manila and Quezon City and its implications for improving instructions in secondary education in Bangkok, Thailand - Iamchaikla, Chintana 1941- (s.n.], 1967)
This paper determines the common practices in classroom observation as a means of supervision in selected public secondary schools in Manila and Quezon City and its implications for improving instruction in secondary education in Bangkok, Thailand. The findings include the educational qualifications and background of division-supervisor respondents, educational qualifications and background of teacher respondents and their common practices.